X-ray irradiation - nonthermal processing and preservation of fresh winter jujube (Zizyphus jujuba mill. cv. Dalidongzao). (October 2022) - Guo, Xiaohong; Guo, Yidan; Yu, Jiangtao; Gu, Tingting; Russo, Haley B.; Liu, Qianting; Du, Jiaming; Bai, Junqing; Zhang, Boce; Kou, Liping
Abstract: In this research, winter jujubes were treated with X-ray doses of 0, 0.3, 0.5 kGy and stored at 0 °C. Then jujubes from early (day 0) and late (day 60) storage were transferred to 20 ± 1 °C and qualities were evaluated every 3 days to explore the preservation effect of X-ray. Results indicated that 0.3 kGy X-ray inhibited the jujube decay by preventing 8.20% of fungal and 29.12% of aerobic bacterial growth. The pectin decomposition was prevented (0.21% on day 60), softening was alleviated, and reddening was delayed for 5 days correspondingly. Microscopic observation validated the integrity of the treated jujube tissue. Furthermore, the highest inhibition rates of 0.3 kGy X-ray on the activities of polygalacturonase (PG), cellulase and β-glucosidase (β-Glu) were 47.32%, 74.71% and 68.00%, respectively. Research demonstrated X-ray's potential in winter jujube preservation, which can provide a solid theoretical reference for the development and industrial application. Highlights: 0.3 kGy X-ray extends the shelf-life of winter jujube stored at room temperature to 12 days. 0.3 kGy X-ray inhibits 8.20% of fungal and 29.12% of aerobic bacterial growth. 0.3 kGy X-ray decreases the activities of polygalacturonase (PG), cellulase and β-glucosidase (β-Glu) by 47.32%, 74.71% and 68.00%, respectively. Winter jujube discoloration is positively correlated with softening decreases.